THE EFFECT OF PROMOTION, QUALITY OF PRODUCTS AND PRICES ON ESSE CIGARETTE PURCHASE DECISIONS IN SURAKARTA CITY - Endang Saryanti; Claudia Roselita Putri (STIE AUB Surakarta, 2019)
This study aims to provide empirical evidence that Promotion, Product Quality and Price have a positive effect on Purchasing Decisions on Esse Cigarettes in Surakarta. The data used in this study are primary data. The sample taken for research is 100 consumers from the population. The analytical method used is the Test Instrument Research, Classical Assumption Test, Multiple Linear Regression Analysis with t Test, F Test, Determination Coefficient Test (). The results of Multiple Linear Regression Analysis that if promotion, product quality and constant prices then consumer purchasing decisions against Esse cigarettes still exist, the promotion variable has a positive effect on consumer purchasing decisions if promotion is increased, consumer purchasing decisions will increase, product quality variables have a positive effect on decisions consumer purchases if product quality is improved then consumer purchasing decisions will increase, price variables have a positive effect on consumer purchasing decisions if prices are increased then consumer purchasing decisions will increase. The results of the promotion t test have a positive and significanteffect on purchasing decisions on Esse cigarettes in Surakarta so hypothesis 1 is proven, Product Quality has a positive and significant effect on purchasing decisions on Esse cigarettes in Surakarta so hypothesis 2 is proven, Price has a positive and significant effect on purchasing decisions on Esse cigarettes in Surakarta so hypothesis 3 is proven. The results of the F Test can be concluded together with promotion variables, product quality and price have a significant influence on consumer purchasing decisions on Esse cigarettes in Surakarta. The Determination Coefficient Test results are 0.203 or 20.3%, which means that the variables of consumer purchasing decisions on Esse cigarettes in Surakarta are able to explain promotion variables, product quality and prices by 20.3% while the rest (79.7%) for example brand image, location factor , and the quality of service to consumers.